Effect of different anticoagulants on multiple electrode platelet aggregometry after clopidogrel and aspirin administration in patients undergoing coronary stent implantation: A comparison between citrate and hirudin. (August 2013) - Zhang, Hong-Zhe; Yu, Long Hao; Kim, Moo Hyun
<x xml:space="preserve">Abstract</x> Outcomes of platelet function tests are highly dependent on the type of blood anticoagulant used. The primary objective of this study was to clinically evaluate the platelet function after dual antiplatelet therapy using two different types of anticoagulant (citrate and hirudin). We compared data obtained from multiple electrode platelet aggregometry (MEA) with reference to light transmission aggregometry (LTA) and VerifyNow (VN) assays. Blood samples were obtained from 119 patients on dual antiplatelet therapy at the time of PCI (PCI) and the following morning (post-PCI). The platelet function tests were performed using two anticoagulated (citrate or hirudin) blood types for MEA as well as citrated blood for LTA and VerifyNow assays. ADP-induced MEA values at PCI for citrated and hirudinated anticoagulants were 36.5 ± 14.3 AUC and 41.4 ± 18.2 AUC (p = 0.021) and post-PCI values were 28.2 ± 11.9 AUC and 28.3 ± 12.8 AUC (p = 0.95). Additionally, AA-induced MEA values at PCI by citrated and hirudinated blood was 13.4 ± 7.3 AUC and 17.6 ± 13.4 AUC (p < 0.01). Post-PCI AA-induced MEA values were 12.0 ± 6.7 AUC and 13.5 ± 8.5 AUC (p = 0.12), respectively. Significant correlations were observed between the two anticoagulants used for MEA and LTA or VN values under ADP-induced platelet stimulation. Citrate tubes are clinically adequate for MEA assays and provide a more economical alternative to hirudin for early and/or delayed phases after clopidogrel-loading doses.